2009
DOI: 10.1177/1352458509106779
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate in combination with minocycline in patients with relapsing—remitting multiple sclerosis: results of a Canadian, multicenter, double-blind, placebo-controlled trial

Abstract: Minocycline is proposed as an add-on therapy to improve the efficacy of glatiramer acetate in relapsing-remitting multiple sclerosis. The effect of minocycline plus glatiramer acetate was evaluated in this double-blind, placebo-controlled study by determining the total number of T1 gadolinium-enhanced lesions at months 8 and 9 in patients who were starting glatiramer acetate and had at least one T1 gadolinium-enhanced lesion on screening magnetic resonance imaging. Forty-four participants were randomized to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 18 publications
(26 reference statements)
0
53
0
Order By: Relevance
“…While the reason for the discrepancies is unknown, differences between the various studies include doses and timing of intervention and may reflect the dual role of microglia in inflammation. Indeed, results of clinical trials from various patient cohorts suffering neurological diseases have also revealed differing results; significant toxicity was found after a phase III randomised trial in patients with ALS (Gordon et al, 2007), a phase III futility study in HD recommended that further study of minocycline in HD was not warranted (Schwarz et al, 2010), while the results of a double-blind, placebo-controlled study have suggested the beneficial effects of minocycline 26 as a combination therapy for MS (Metz et al, 2009), and another preliminary study showed efficacy in acute ischemic stroke (Lampl et al, 2007). Despite these contradictory results, a phase II randomized double-blind futility clinical trial of minocycline in PD has been set-up.…”
Section: Minocyclinementioning
confidence: 99%
“…While the reason for the discrepancies is unknown, differences between the various studies include doses and timing of intervention and may reflect the dual role of microglia in inflammation. Indeed, results of clinical trials from various patient cohorts suffering neurological diseases have also revealed differing results; significant toxicity was found after a phase III randomised trial in patients with ALS (Gordon et al, 2007), a phase III futility study in HD recommended that further study of minocycline in HD was not warranted (Schwarz et al, 2010), while the results of a double-blind, placebo-controlled study have suggested the beneficial effects of minocycline 26 as a combination therapy for MS (Metz et al, 2009), and another preliminary study showed efficacy in acute ischemic stroke (Lampl et al, 2007). Despite these contradictory results, a phase II randomized double-blind futility clinical trial of minocycline in PD has been set-up.…”
Section: Minocyclinementioning
confidence: 99%
“…This tetracycline antibiotic that inhibits MMP activity and reduces the severity of animals immunized for EAE (22)(23)(24) has shown promise in relapsing-remitting MS in early clinical trials (25)(26)(27)(28) and, more recently, was found to be effective in a phase III trial in early MS (L. M. Metz et al, submitted for publication). We find that both murine and human T cells were reduced in the expression level (MFI) of EMMPRIN by minocycline, as well as in the percentage of T cells with EMMPRIN expression.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on the potential MS medication minocycline, a tetracycline antibiotic that inhibits MMP activity (21) and reduces the severity of animals immunized for EAE (22)(23)(24). From these animal studies, minocycline was tested and found to have promise in relapsing-remitting MS as suggested by early clinical trials (25)(26)(27)(28). More recently, a phase III trial in patients with a first demyelinating event (clinically isolated syndrome) found that minocycline reduced the acquisition of a second event to become clinically definite MS (L. M. Metz, D. K. B. Li, A. Traboulsee, P. Duquette, M. Eliasziw, G. Cerchiaro, J. Greenfield, A. Riddehough, M. Yeung, M. Kremenchutzky, et al, submitted for publication).…”
mentioning
confidence: 99%
“…A recent phase II trial analysed the effect of minocycline as add-on therapy to GA [68]. RR-MS patients were treated with GA and randomized to receive either minocycline 100mg twice daily or placebo.…”
Section: Minocyclinementioning
confidence: 99%